RESPON GURU DAN SISWA PADA PEMBELAJARAN TATAP MUKA DI MASA PANDEMI COVID 19 DI SD MUHAMMADIYAH PURWOKERTO - Sony Irianto (PROCEEDING UMSURABAYA, 2022)
Face-to-face learning (PTM) in Banyumas Regency, Central Java, started Wednesday (1/9/2021). This follows the decline in the status of the Implementation of Community Activity Restrictions (PPKM) from level 4 to 3. The Head of the Banyumas Education Authorities, Irawati, said that for the early stage, PTM would be tested in 54 schools. "According to the governor's circular letter, limited PTM may be started". Elementary schools will carry out PTM starting Monday, October 4, 2021 after previously there was a coordination meeting between the principal and the Head of the Elementary School Curriculum regarding the preparation of PTM. This study aims to find out; 1) teacher and student responses on the implementation of face-to-face learning 2) PTM implementation 3) PTM constraints and solutions This type of research is a qualitative research with descriptive method. The data collection process uses interviews and documentation. The informants of this research are teachers and students at SD Muhammadiyah Purwokerto. The results of the study; 1) Teachers and students responded well to the implementation of PTM; 2) The implementation of PTM during the Covid 19 Pandemic in Elementary Schools was in accordance with the Limited PTM SOP; 3) Obstacles faced in the implementation of PTM were external constraints in the form of increasingly loose health protocols in the community , while internal constraints in the form of limited facilities and staff providing lead to less than optimal implementation of health protocols. In addition, the attendance capacity of students in class is limited to 50% and learning starts at 07.00-09.00 for 50% of the first class and 09.30-11.30 for 50% of the second class. PTM with strict health protocols causes the learning process and learning outcomes to be less than optimal. The principal as a leader in the school in dealing with external and internal problems always coordinates with related parties so that PTM running properly and expeditely. Keywords: Teacher's Response; Student Response; PTM